Application and Review of Pediatric Pharmacotherapy - Glover, Mark L. (London : Pharmaceutical Press, 2011)
Increase your understanding of pharmacotherapy prescribed to pediatric patients with these realistic case studies.
Keywords: Pharmacotherapy; Kind; Pharmakotherapie; Children -- Diseases -- Chemotherapy